Tumor thrombus in the large veins draining primary pelvic osteosarcoma on cross sectional imaging. Issue 105 (August 2018) - Yedururi, Sireesha; Chawla, Sumedha; Amini, Behrang; Wei, Wei; Salem, Usama I.; Morani, Ajaykumar C.; Wang, Wei-Lien; Gorlick, Richard; Lewis, Valerae O.; Daw, Najat C.
Highlights: Tumor thrombus is frequently seen in the large veins draining primary pelvic osteosarcoma on cross sectional imaging studies. Accurate detection of tumor thrombus in the large draining veins on the pre-operative imaging may impact surgical margins. In surgically resected cohort, patients with tumor thrombus showed statistically significant lower overall survival. Abstract: Purpose: To evaluate the frequency of tumor thrombus in the large veins draining primary pelvic osteosarcoma on early cross-sectional imaging studies and its effect on patient survival. Materials and methods: Our retrospective study included all patients with primary pelvic osteosarcoma treated at our facility between January 2000 and May 2014, who were ≤ 45 years of age, and had adequate imaging studies and clinical follow up. Four radiologists evaluated for tumor in the large draining veins on initial CT, MRI and PET/CTs. A consensus evaluation by the four radiologists together with findings on operative reports, pathology reports or follow-up imaging was used as the reference standard. Results: Thirty-nine patients with primary pelvic osteosarcoma met final inclusion criteria. Tumor thrombus was identified in the large draining veins in 10 of the 22 (45%) patients who underwent tumor resection and 10 of the 17 (59%) who did not. In the 22 patients who underwent tumor resection, tumor thrombus was significantly associated with worse overall survival (p = 0.03). Conclusions: Tumor thrombus in the large draining veins is identified in a significant proportion of initial imaging studies in patients with pelvic osteosarcoma, and is associated with worse overall survival in patients who undergo tumor resection.